Laser-induced sublimation extraction for centimeter-resolution multi-species greenhouse gas analysis on ice cores - L. Mächler; D. Baggenstos; F. Krauss; J. Schmitt; B. Bereiter; R. Walther; C. Reinhard; B. Tuzson; L. Emmenegger; H. Fischer (Atmospheric Measurement Techniques, 2023)
Precision, accuracy, and temporal resolution are key to making full use of atmospheric trace gas records in ice cores. These aspects will become especially crucial for ice cores that aim to extend the ice core record to the last 1.5 Myr, i.e., across the Mid-Pleistocene Transition (as currently drilled within the European project Beyond EPICA – Oldest Ice Core (BE-OIC)). The ice from this period is expected to be close to bedrock and, due to glacier flow, extremely thinned with 15 000 years of climate history contained in only 1 m of ice. Accordingly, for a century-scale resolution, the sample vertical extent must be reduced to a few centimeters containing only about 1–2 mL air STP. We present a novel combined system for the extraction and the simultaneous measurement of CO 2 , CH 4 , and N 2 O concentrations, as well as δ 13 CO 2 , which achieves a vertical resolution of 1–2 cm ( 3.5×3.5 cm cross section) with precisions of 0.4 ppm, 3 ppb, 1 ppb, and 0.04 ‰, respectively, in sublimation tests with standard gas over gas-free ice. This is accomplished by employing a directional and continuous laser-induced sublimation followed by analysis of the sample gas by a quantum cascade laser absorption spectrometer (QCLAS). Besides the low sample volume requirements and the vertical resolution capabilities, the described method holds additional advantages over previous methods, including the immunity of the highly specific QCLAS analysis to drilling fluid contamination as well as the non-destructive nature of the spectroscopic gas analysis. The combined extraction and analysis system was extensively tested by sublimating gas-free ice with introduction of a standard gas to determine the accuracy and characterize potential artifacts. Moreover, Antarctic ice samples were measured to confirm the measurement performance, covering the range of variability expected in Pleistocene ice and highlighting the vertical resolution capabilities critical for its application within BE-OIC.